Diffusion‐weighted imaging in assessing pathological response of tumor in breast cancer subtype to neoadjuvant chemotherapy. Issue 3 (8th January 2015) - Liu, Shangang; Ren, Ruimei; Chen, Zhaoqiu; Wang, Yongsheng; Fan, Tingyong; Li, Chengli; Zhang, Pinliang
<x xml:space="preserve">Abstract</x> Purpose To investigate the efficacy of diffusion‐weighted imaging (DWI) for reflecting and predicting pathological tumor response in breast cancer subtype to neoadjuvant chemotherapy (NAC). Materials and Methods The retrospective study included 176 patients with breast cancer who underwent magnetic resonance imaging (MRI) examinations before and after NAC prior to surgery. The pre‐ and post‐NAC apparent diffusion coefficient (ADC) values of tumor were measured respectively on DWI. The pathological response was classified into either a complete response (pCR) or as a noncomplete response (pNCR) to NAC with the Miller & Payne system. The relationship between the ADC value and the pathological response was assessed according to intrinsic subtypes (Luminal A, Luminal B, HER2‐enriched, and triple negative) defined by immunohistochemical features. Results Multiple comparisons respectively showed that pre‐NAC and post‐NAC ADC were significantly different among four subtypes (P < 0.001). After the comparison between two different subtypes, the pre‐NAC ADC value of the triple‐negative and HER2‐enriched subtypes were significantly higher than Luminal A (P < 0.001 and P < 0.001) and Luminal B subtype (P < 0.001 and P = 0.009), and the post‐NAC ADC of triple‐negative subtype was significantly higher than the others (P < 0.001). The pre‐NAC ADC of pCRs was significantly lower than that of pNCRs only in the triple‐negative subtype among four subtypes (P < 0.001), and the post‐NAC ADC of pCRs was significantly higher than that of pNCRs in each subtype (P < 0.001). Conclusion DWI appears to be a promising tool to determine the association of pathological response to NAC in breast cancer subtypes. J. Magn. Reson. Imaging 2015;42:779–787.